Дослідження алгоритму параметричної ідентифікації у моделі фінансових потоків інтегрованої логістизації процесів на підприємствах - Волоснікова, Н. М. (Видавництво Львівської політехніки, 2016)
Розглянуто проблему дослідження параметричної ідентифікації у моделі фінансових потоків інтегрованої логістизації процесів на підприємствах. Визначено концептуальні підходи до фінансових потоків інтегрованої логістизації процесів. Розглянуто адаптивні властивості фінансових потоків інтегрованої логістизації процесів. Optimization of financial flows, a key aspect of logistics achieved by attracting and allocation of financial resources implemented in financial flows logistics integrated processes in enterprises. Currently, the preparation, organization and management of logistics processes important to follow certain requirements to financial flows such parameters as the adequacy, efficiency and reliability. Despite the increased interest in the problems, there is a serious lack of systematic descriptions of the structure and functioning of financial flows in real logistics systems. The article is a study of parametric identification of models of financial flows logistics integrated processes in enterprises. The financial activities of the company can be viewed as a set of dynamic relationships both within the enterprise and the environment. Managing such a complex, the process of formation, distribution and use of financial resources is inextricably linked to the management of logistics activities in the workplace. Last determine the direction and amount of use. Creating mechanisms for information management integrated logistics processes in enterprises is particularly important when the organizational structure of financial flows and its elements are treated as important and rare resource, and as part of the economic potential of logistics system, which should be used effectively to achieve specific goals. Adapting to an environment characterized by high uncertainty, financial flows enables integrated processes logistics ensure the achievement of some significant objectives in terms of lack of prior information about the environment. In this work the important issues arising in solving problems of parametric identification when the structure model of financial flows logistics integrated business processes defined and known basis functions of financial flows. The presence of the circuit in anticipation of an integrated financial flows logistics process significantly expands the adaptive capacity of the company and, consequently, help increase its competitiveness by increasing the speed and reducing the cost of adaptive response to adverse environmental effects.
The study of parametric identification algorithm in the model of financial flows integrated processes in the enterprise
Keywords: логістизація; фінансові потоки; параметрична ідентифікація; стратегічне управління; фінансова діяльність підприємства; logistics; financial flows; parametric identification; strategic management; financial activities of the company